Family Conflicts Are Bitter Splits That Hurt: A Qualitative Inquiry Toward Understanding the Impact of Family Issues in Functional Neurological Symptom Disorder - Bokharey, Iram Zehra; Fahim, Urusa; Tahir, Khola (Frontiers in Psychology, 2021)
Abstract The study was conducted with the aim to ascertain the lived experiences of individuals with Functional Neurological Symptom Disorder (FNSD) around stressful situations in their families in Pakistan. For this purpose, a total sample of 10 participants (Women=8; Men=2) were recruited from the psychiatry department of a tertiary care hospital in Lahore, Pakistan. Semi-structured interviews were conducted and analyzed through Interpretative Phenomenological Analysis (IPA). The two main themes revealed in the analyses were quarrels and unexpressed emotions. The sub-themes of quarrels included quarrels with family members, quarrels within family, parental/marital discord and quarrels with extended family members. The subthemes for unexpressed emotions were hurt, anger, sadness, and jealousy. In conclusion, this study revealed that in Pakistan, stressors related to family serve as significant contributing factor sin the development of FNSD.